Tingkat Regulasi Emosi Pada Penari Tradisional Tari Klasik Gaya Yogyakarta - Pangesti, Rizky Anom; Arswimba, Bernardinus Agus (Universitas Sanata Dharma, 2024)
This study aims to (1) Describe the level of emotional regulation in traditional dancers of Yogyakarta style classical dance; (2) which items measuring the level of emotional regulation in traditional dancers of Yogyakarta style classical dance have low scores which will then be used as a proposal for guidance topics. The subjects of the study were all Dance Arts Students of ISI Yogyakarta. This type of research is quantitative descriptive. Data collection in this study used a google form of emotional regulation in traditional dancers of Yogyakarta style classical dance which contained 74 items. The questionnaire was compiled using aspects of emotional regulation according to Thompson in Sawitri (2017), the reliability of the instrument was tested using the Alpha Cronbach approach. (α) was obtained from the results of the coefficient value of (0.975) with the number of valid items of 69 items. The data analysis technique used descriptive statistics with categorizations of very high, high, medium, low, very low. The results of the study showed that (1) there were 34 students (64.2%) whose emotional regulation level was categorized as very high, 14 students (26.4%) were categorized as high, and 5 students (9.4%) were categorized as medium. (2) This study also identified that there were 51 items (74%) that were categorized as very high, 7 items (10%) were categorized as high, 11 items (16%) were categorized as medium, and there were no items (0%) that were categorized as low and very low. Based on the results of the research analysis, the topics of tutoring were compiled, namely (1) Emotions Modification, (2) Emotions Monitoring